Effect of DC voltage source on the voltage and current of transmitter and receiver coil of 2.5 kHz wireless power transfer - A. H. Butar-Butar; J. H. Leong; M. Irwanto (Institute of Advanced Engineering and Science, 2020)
A solenoid supplied by alternating current (AC) voltage generates electromagnetic which has a field area depends on the level of supplied voltage and current flows through the solenoid. The electromagnetic filed can be captured by the other solenoid in the field area. This concept can be applied in a wireless power transfer (WPT) as presented in this paper. The WPT has transmitter coil and receiver coil which each has form of solenoid. The transmitter coil is connected a half bridge circuit to generate AC voltage on the transmitter coil which transferred to the receiver coil. In the experimental set up, the receiver coil is supplied by DC voltage source and it is changed to observe its effect on the voltage and current on the transmitter and receiver coil of the WPT system.